Legal protection of persons with disabilities in sungailiat tourism area: criminal and CRDP perspectives (sungailiat tourism) - Hikmah, Nurul; Juharsah, Luthfi Felysia Putri; Hidayat, Muhamad Syafiq; Situmorang, Ave Agave Christina (Journal of Law Science, 2024)
This paper aims to analyze the need for regulation to protect individuals with disabilities within minority communities. Durimg this time, the concept of tourism is only designed for people who are normal and has not been designed for disabled people. Tourism is right for human being including disabled people. Defines that there requirements for disabled people in tourism, those are: availability for accessibility, transportation, and accommodation. Toursim places proposed in this research are marine tourism (Tanjung Pesona Beach, Parai Tenggiri Beach, Puri Ansell Beach), urban tourism (Taman Kota), and natural tourism (Pemandian Air Panas Tasya). Data collected in this research use interview technique and observation. Of the five tourist attractions we researched, we still found several that were not friendly to people with disabilities. Hence, the research result recommends the tourism policy maker to provide friendly facility and accesibility for disabled people